Management of inter-episodic periods in patients with bipolar disorder. (2nd June 2016) - Samalin, Ludovic; Murru, Andrea; Vieta, Eduard
ABSTRACT: The management of inter-episodic periods of bipolar disorder (BD) appears complex as it combines several therapeutic approaches and takes into account individual characteristics of BD patients. Over recent decades, new evidence has been provided about pharmacological treatments, psychosocial interventions or models of care for the long-term management of BD patients. Considering this, guidelines for the maintenance treatment of BD should be regarded as an evidence-based ground for everyday clinical practice in real-life setting. This article critically reviews recently published clinical guidelines on the management of BD patients during the inter-episodic phases of illness, in order to highlight the consensual or controversial recommendations.